Karakteristik Morfologi Dan Sebaran Lamun Halophila spinulosa (R.Br.) Aschers. Di Kepulauan Bangka Belitung, Indonesia - Adi, Wahyu; Muftiadi, M. Rizza; Henri, Henri; Pamungkas, Aditya; Supratman, Okto; Okto Supratman (Universitas Bangka Belitung, 2023)
Halophila spinulosa (R. Br.) Aschers is a type of seagrass found in Indonesia with limited distribution. One of the areas where Halophila spinulosa is found in the Bangka Belitung Islands. Although found in the Bangka Belitung Islands, information on this type of seagrass is very limited. The objectives of the study were to identify morphological characters, identify types of seagrass associated with Halophila spinulosa and present a distribution map of Halophila spinulosa in the Bangka Belitung Islands. The research method for seagrass morphological characters is based on field data in the form of photographs, then compared with identification sources from books and research journals. The seagrass distribution map was determined based on a literature search from 2015 to 2022 and then a map was made using Arcmap 10.8 software. The results of the research on the morphological characters of Halophila spinulosa species can be seen from the shape of the roots, rhizomes, leaves, flowers and fruit. This type of root form is unbranched root (simple root) and each node on the rhizome has one root. Compound leaves are elliptical in shape. These leaves are paired, in opposite positions, located in one plane, arranged obliquely around the stem and have serrated leaf tips. The distribution of Halophila spinulosa seagrass in the Bangka Belitung Islands is spread in the areas of Central Bangka Regency, South Bangka Regency and Belitung Regency. Halophila spinulosa species are often found mixed (associated) with seagrass species Halodule uninervis and Oceana serrulata.